2009
DOI: 10.1007/s12199-009-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between interpersonal relationship among high-school students and mental health

Abstract: Objectives Adolescents have many anxieties,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…Although a comparison between the sexes revealed that sex is not an independent factor for mental health problems, the overall positive rate of mental health problems was higher in males than females, which is similar to a Japanese nationwide survey suggesting that more male high school students feel unhappy than females [ 43 ]. This discrepancy may be due to sex differences in interpersonal relationships and friendships, as males were usually less likely to consult others about their struggles than females [ 44 ]. In our study, age was also not an independent factor for students’ mental health problems, while students in higher grades were significantly associated with higher odds of having mental health problems than first-year students, which is consistent with other studies [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a comparison between the sexes revealed that sex is not an independent factor for mental health problems, the overall positive rate of mental health problems was higher in males than females, which is similar to a Japanese nationwide survey suggesting that more male high school students feel unhappy than females [ 43 ]. This discrepancy may be due to sex differences in interpersonal relationships and friendships, as males were usually less likely to consult others about their struggles than females [ 44 ]. In our study, age was also not an independent factor for students’ mental health problems, while students in higher grades were significantly associated with higher odds of having mental health problems than first-year students, which is consistent with other studies [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above are subjective evaluations of the degree to which an individual feels fulfilled in terms of needs, goals, and life satisfaction. There is evidence showing that adolescents are facing a great deal of anxiety, and that having someone, such as a friend or adult, to consult would alleviate their depression and increase their level of satisfaction with their life at school [ 34 ]. Hui concluded that having an increased ability to cope with stress and adversity will result in higher life satisfaction and better academic performance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social relationship with friends could play a significant and detrimental role in adolescents' psychosocial development (Giletta and Scholte, 2012). Research evidences exist that emphasize particular importance of friendly relations in maintaining mental health (Okada et al, 2010) as one of the main sources of happiness and well-being (Ballas and Dorling, 2007). It is a common norm to have a boy friend/girl friend in most of the Western countries but in many of the countries in the East due to religious or cultural believes this type of relationship between individuals of opposite sex is not accepted and allowed formally by the families or larger societies.…”
Section: Discussionmentioning
confidence: 99%